Experimental investigation on the melting behavior of phase change materials in open-cell metal foams in an inclined rectangular enclosure. (October 2018) - Guo, Zengxu; Bai, Qingsong; Hou, Jialin; Yang, Xiaohu; Liu, Yanhua; Sun, Yanjun
Abstract: To explore the heat and mass transfer characteristics during phase change, a well-designed test rig with melting front visualization was designed and fabricated. The results show that the different inclination angles have a great influence on the melting process of pure paraffin. Compared with the 60-degree inclination, the full melting time of pure paraffin at 30-degree obliquity decreased by 25.30%. The visualization demonstrated an inclined melting front, which indicated the contribution of local natural convection in the fluid phase. However, there seems to be little influence of inclination angles for the melting process of paraffin embedded in metal foam. Local thermal non-equilibrium between metallic ligaments and the saturating PCM (paraffin) was experimentally observed. This revealed the feasibility of two-equation model for modelling the phase change process in open-cell metal foam.